Pengaruh Kualitas Pelayanan dan Fasilitas Wisata terhadap Kepuasan Pengunjung di Objek Wisata Taman rekreasi dan Rumah Susu Lachio Patumbak - Andrea, Nabila; Sulaiman, Fahmi (Universitas Batanghari, 2024)
The target of this study is to observe the influence of service quality and tourist facilities on visitor satisfaction at the Lachio Patumbak Recreation Park and Milk House tourist attraction. This study is of a quantitative type by including several variables including Service Quality and Tourist Facilities as independent variables and Visitor Satisfaction as the dependent variable. To collect data, a questionnaire was used and a total random sample of 93 respondents. The analysis uses a multiple linear regression method using SPSS version 20 application software. The results of the study show that Service Quality has a significant partial impact on Visitor Satisfaction, because t calculated for Service Quality is above the t table (7.778 > 1.986) and the sign is 0.000 < 0.05. However, the use of tourist facilities has a partial impact on visitor satisfaction with a sign of 0.010 > 0.05 and t calculated above t table (2.643 > 1.986). Then the quality of tourist services & facilities has a significant impact on visitor satisfaction together because f count > f table (84.645 > 3.10) is signiﬁcantly 0.000 < 0.05.